Pulsating pingos, Tuktoyaktuk Peninsula, N.W.T. - Mackay, J. Ross (Canadian Journal of Earth Sciences, 1977)
Field studies have been carried out on two pingos on Tuktoyaktuk Peninsula, N.W.T. One pingo was studied from 1969–1976; the other was studied from 1974–1976. Precise levelling of bench marks in permafrost shows that the tops of these pingos alternately rise and subside in response to the rate of accumulation and loss of water beneath them. The water lenses may exceed 50 cm in depth. The high pore water pressure that causes pingo uplift is produced by pore water expulsion adjacent to the pingo, where the thickness of permafrost is 2 to 3 times the pingo height. The pore water pressure beneath the permafrost surrounding the pingo may approach 100% of the lithostatic pressure. When uplift from the water lens exceeds the strength of the pingo, peripheral failure occurs, water escapes as a spring, and the pingo subsides. Pulsating pingos seem characterized by long radial tension cracks which extend far onto the drained lake floor.The pulsation of pingos has also been experimentally achieved by drilling holes through two pingos to release spring flow from subpingo pore water. The field evidence, from precise before-and-after surveys, indicates that the two pingos and their adjacent drained lake floors are virtually 'afloat' on subpermafrost water.